The simplification of the polynomial expression will give 3x² - 20x + 8.
<h3>How to illustrate the polynomial?</h3>
The polynomial expression is given as:
(5x² + 13x4) (17x² + 7x - 19) + (5x-7)(3x + 1)
= 5x² + 13x - 4 - 17x² - 7x + 19 + 15x² + 5x - 21x - 7
Then collect like terms
= 5x² + 15x² - 17x² + (13x - 7x + 5x - 21x) - 4 - 7 + 19
= 3x² - 20x + 8.
Learn more about polynomial on:
brainly.com/question/2833285
#SPJ1
Answer:
adult tickets
Step-by-step explanation:
Let x be the total sold adult ticket.
Given:
Total 582 tickets were sold.
There were 68 fewer student tickets sold than adult tickets
Then there were
students.
So, The total sold ticket equation is
![x+(x-68)=582](https://tex.z-dn.net/?f=x%2B%28x-68%29%3D582)
![2x-68=582](https://tex.z-dn.net/?f=2x-68%3D582)
![2x=582-68](https://tex.z-dn.net/?f=2x%3D582-68)
![x=\frac{514}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B514%7D%7B2%7D)
![x=257](https://tex.z-dn.net/?f=x%3D257)
Therefore, 257 adult tickets were sold
Answer:
x = π/3, x = 5π/3, x = 4π/3
Step-by-step explanation:
Let's split the given equation (2cosx-1)(2sinx+√3 ) = 0 into two parts, and solve each separately. These parts would be 2cos(x) - 1 = 0, and 2sin(x) + √3 = 0.
![2\cos \left(x\right)-1=0,\\2\cos \left(x\right)=1,\\\cos \left(x\right)=\frac{1}{2}](https://tex.z-dn.net/?f=2%5Ccos%20%5Cleft%28x%5Cright%29-1%3D0%2C%5C%5C2%5Ccos%20%5Cleft%28x%5Cright%29%3D1%2C%5C%5C%5Ccos%20%5Cleft%28x%5Cright%29%3D%5Cfrac%7B1%7D%7B2%7D)
Remember that the general solutions for cos(x) = 1/2 are x = π/3 + 2πn and x = 5π/3 + 2πn. In this case we are given the interval 0 ≤ x ≤2π, and therefore x = π/3, and x = 5π/3.
Similarly:
![\:2\sin \left(x\right)+\sqrt{3}=0,\\2\sin \left(x\right)=-\sqrt{3},\\\sin \left(x\right)=-\frac{\sqrt{3}}{2}](https://tex.z-dn.net/?f=%5C%3A2%5Csin%20%5Cleft%28x%5Cright%29%2B%5Csqrt%7B3%7D%3D0%2C%5C%5C2%5Csin%20%5Cleft%28x%5Cright%29%3D-%5Csqrt%7B3%7D%2C%5C%5C%5Csin%20%5Cleft%28x%5Cright%29%3D-%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D)
The general solutions for sin(x) = - √3/2 are x = 4π/3 + 2πn and x = 5π/3 + 2πn. Therefore x = 4π/3 and x = 5π/3 in this case.
So we have x = π/3, x = 5π/3, and x = 4π/3 as our solutions.